UTILIZATION OF ICTS IN ACCESSING COCOA BEANS MARKET INFORMATION BY CROSS RIVER STATE FARMERS - Anthony Eghe AGBONGIARHUOYI; Kehinde Adesina THOMAS; Eghosa Osas UWAGBOE; Busayo Solomon FAMUYIWA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The research work investigated farmers’ level of use of Information and Communication Technologies (ICTs) in accessing cocoa beans market information in Cross River State, Nigeria. Sixty farmers were selected using random systematic sampling technique. Pertinent information was collected with structured questionnaire. Data were analysed with descriptive statistics and Pearson Product Moment Correlation (PPMC). Results reveal that 90% of the respondents used mobile phone while 85% used radio to access cocoa beans market information. Frequency of use for mobile phone (75%) and radio (35%) were on weekly basis. The major market information used for ICTs were cocoa beans sales price (88.3%), quality (85%), value addition (78.3%) and certification (75%). Cocoa beans sales price was accessed regularly, while certification of cocoa beans was occasional. Major constraints to the utilization of ICTs were poor electricity supply and internet services. Income (r=0.279, p=0.021), cocoa farm size (r=0.300, p=0.020) and age (r= -0.301, p=0.019) correlated significantly with extent of using ICTs in accessing cocoa market information by farmers. Efforts should be made by internet providers to ensure optimum internet connection for improved ICTs used by farmers in sourcing cocoa market information.